Gambaran Self-Acceptance Siswa SMA Negeri 10 Padang Pengguna iPhone - Aini, Zahratul; D, Sukma (AHKAM, 2025)
This research is based on the phenomenon where many students use iphones in a negative light, primarily for show, to maintain social status, follow peers, and appear prestigious to others. iphone users among students become a benchmark in their surrounding environment. This behavior is attributed to poor self-acceptance. Self-acceptance is defined as the process whereby individuals acknowledge and embrace all aspects of themselves, both positive and negative. The purpose of this study is to describe self-acceptance. The study employs a quantitative method with a descriptive quantitative research design. The population consists of 752 students enrolled in grades X and XI at SMAN 10 Padang for the 2024/2025 academic year, with a sample of 104 iPhone users selected from these grades using purposive sampling techniques. Data collection involved administering a self-acceptance questionnaire specifically designed for iphone users. The data were analyzed using descriptive analysis techniques. The results indicate that iphone users at SMAN 10 Padang exhibit a high level of self-acceptance, with a percentage of 75.73%. The study recommends implementing group guidance services, individual counseling, and information services for guidance and counseling teachers or counselors to assist students in enhancing and maintaining their self-acceptance.